2007
DOI: 10.1097/ypg.0b013e32816ebc9e
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of 15 polymorphisms within 10 candidate genes for antisocial behavioural traits

Abstract: This study sought to test 15 simple sequence repeat polymorphisms within 10 candidate genes for association with antisocial behavioural traits. Genes included were those known to regulate dopamine synthesis and transmission in the brain (DBH, DRD2, MAOA, TFAP2B, NR4A2, LMX1B) and those involved in the differentiation of social and sexual behaviour in men and women (AR, ESR1, OXTR, AVPR1A). Participants were Caucasians (men=1007, women=1089) aged 20-24 years who were assessed for indicators of antisocial traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
2
31
0
1
Order By: Relevance
“…These observations were then confirmed by several studies in Europeans and Asians showing a correlation between the carriage of short CAG repeat alleles and antisocial behavior (Prichard et al 2007;Westberg et al 2009), Eysenck's psychoticism (Turakulov et al 2004;Loehlin et al 2005), and aggression (Rajender et al 2008). Furthermore, Aluja et al (in press) showed an implication of both AR repeats in predisposition to impulsive-disinhibited personality traits in Spanish inmates carrying the haplotype comprised of short CAG repeats and long GGC repeats.…”
Section: Androgen Receptormentioning
confidence: 73%
“…These observations were then confirmed by several studies in Europeans and Asians showing a correlation between the carriage of short CAG repeat alleles and antisocial behavior (Prichard et al 2007;Westberg et al 2009), Eysenck's psychoticism (Turakulov et al 2004;Loehlin et al 2005), and aggression (Rajender et al 2008). Furthermore, Aluja et al (in press) showed an implication of both AR repeats in predisposition to impulsive-disinhibited personality traits in Spanish inmates carrying the haplotype comprised of short CAG repeats and long GGC repeats.…”
Section: Androgen Receptormentioning
confidence: 73%
“…Buckholtz and Meyer-Lindenberg recently reviewed the available literature on MAOA in impulsive aggression, and proposed a mechanism by which the lower activity variants of MAOA could sensitize pertinent neural circuitry to early life stress, while concluding that variation at the MAOA VNTR accounts for only a small amount of variance in risk (Buckholtz & Meyer-Lindenberg, 2008). Not all studies have replicated the findings discussed above (Koller, Bondy, Preuss, Bottlender, & Soyka, 2003;Prichard, Jorm, Mackinnon, & Easteal, 2007;Sjoberg et al, 2007). A few studies suggest that the high activity variants, or longer alleles, may be problematic alone (Tikkanen et al, 2009), under the influence of unfavorable environmental factors (Sjoberg et al, 2007;Vanyukov et al, 2007), or in combination with a delinquent peer group (Beaver & Holtfreter, 2009), while still other studies conclude that the higher activity variants are relatively protective in the face of environmental adversity (e.g.…”
Section: Metabolic Pathwaysmentioning
confidence: 73%
“…The recent work of Rajender and colleagues found that shorter CAG repeats were more common in 374 men who had been convicted of violent criminal offenses as compared with controls matched by ethnicity (Rajender et al, 2008), building on the work of Jonsson and colleagues (Jonsson et al, 2001), which suggested a tendency for shorter CAG repeats to be associated with personality traits related to dominance and aggression on the Karolinska Scale of Personality. The work of Prichard and colleagues in 2007 indicated that highest frequency repeat length in antisocial behavior was seen among men with the medium length repeats, and was not seen among female subjects at all (Prichard et al, 2007). The work of Cheng also did not support the association of short repeats and antisocial behavior (Cheng, Hong, Liao, & Tsai, 2006), and the work of Loehlin suggested that any effects of androgen receptor polymorphisms on personality were weak at best (Loehlin, Jonsson, Gustavsson, Schalling, & Stallings, 2003) and the range of findings in this area appears to bear out this assertion.…”
Section: Androgen Receptorsmentioning
confidence: 95%
“…This genotype has been shown to be associated with personality dimensions such as anxiety, psychasthenia, depression or antisocial traits, with the short allele generally correlating with lower scores in the different measured psychological scales [152][153][154][155]. Furthermore, and supporting the aforementioned biological function of TFAP2B, this polymorphism has been suggested to interact with polymorphic sites in the serotonin transporter (5HTTLPR), catechol-O-methyl transferase (COMT ) and monoamino oxidase (MAO)-A genes to modulate additional personality dimensions [154,156].…”
Section: Transcription Factor Ap-2 Betamentioning
confidence: 98%